Bridging the gaps between randomized controlled trials and real-world use of thrombopoietin receptor agonists for adult primary immune thrombocytopenia: a systematic review and meta-analysis - Luo, Liping; Jin, Shanshan; Song, Zhujin; Chong, Gaowei; Ding, Haiying; Zeng, Su; Dai, Mengfei; Wu, Miaolian (Frontiers in Medicine, 2025)
BackgroundRandomized controlled trials (RCTs) evaluate short-term efficacy/safety of thrombopoietin receptor agonists (TPO-RAs) in immune thrombocytopenia (ITP), leaving long-term outcomes unclear. This study integrates real-world evidence (RWE) with RCT to assess TPO-RA performance across treatment durations.MethodsA systematic literature search identified RCTs and real-world studies (RWS) assessing TPO-RAs in adults with primary ITP. Short-term (≤6 months) and long-term (6–12/>12 months) outcomes included platelet response, rescue therapy, bleeding events, and adverse events (AEs). Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using random/fixed-effects models.ResultsMeta-analysis included 12 RCTs and 32 RWS. Short-term TPO-RA administration yielded 70% platelet response versus placebo (OR = 18.07, 95% CI:12.4–26.16, p < 0.001), escalating to 85% (6–12 months) and 91% (>12 months) in RWS. TPO-RAs reduced bleeding risks (any: OR = 0.43, significant: OR = 0.40, both p < 0.001). Rescue therapy increased from 12% (short-term) to 32% (>12 months). Serious AE (SAE) incidence matched placebo short-term (OR = 0.69, 95% CI:0.47–1.01) but rose from 8% (RCTs) to 27% (RWS > 12 months).ConclusionTPO-RAs sustain durable platelet response but exhibit increase in rescue therapy and SAEs over time. Longitudinal RWS integration into ITP management is critical, necessitating protocolized safety monitoring and personalized regiments to optimize chronic TPO-RA utilization.Systematic review registrationhttp://www.crd.york.ac.uk/PROSPERO, identifier [CRD42025649608].